analisis yuridis perlindungan hukum terhadap anak korban kekerasan - Astuti, Nurul Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Children are potential successors to future generations who must be protected, including their physical and psychological health. Children are a group that requires attention in community health development efforts. This research was conducted with the aim of: Analyzing legal protection for victims who experience violence. This study uses descriptive analytical methodes and relationships with laws and regulations. Tis study uses descriptive analytical methodes and relationships with laws and regulations. This study uses a normative approach to legal (juridical) aspects through document studies. Legal protection for children regarding freedom and children’s human rights related to child welafare.